Фінансове забезпечення розвитку інноваційних процесів в сфері готельно-ресторанного бізнесу - Литвиненко, Ярослав Васильович; Литвиненко, Тамара Євгенівна (My University, 2013)
У статті розглянуті проблеми готельно-ресторанного бізнесу в Україні, які стають особливо актуальними в сучасних умовах економічної кризи, також розглянуті напрямки інноваційного розвитку України. Визначаються сутність та характерні особливості інноваційного розвитку, необхідність отримання підтримки суб’єктів інноваційної діяльності з боку держави, характер такої підтримки, можливі позитивні наслідки та отримання економічного ефекту. The article considers the problems of the hotel and restaurant business in Ukraine which become especially actual in the current conditions of economic crises. The aim of the article is the role of the state in provision of financial innovation in the field of hotel and restaurant business. The research and analysis of the current state of the hotel and restaurant business in Ukraine have been done. Further development of Ukraine’s economy and successful exit from the crisis in which Ukraine is a long time is associated with the subsequent development of innovation at both the state and the level of the individual enterprise. This especially true for those areas which are not productive and belong to the service sector, to which belongs hotel and restaurant business. The most effective form of organization and production activities in the hotel and restaurant business in modern conditions is the formation of joint ventures with both domestic and foreign investors.
Keywords: готельно-ресторанний бізнес; hotel and restaurant business; державна підтримка інноваційної діяльності; state support for business entities of innovation